Substitusi Viterna Plus pada Pakan bagi Pertumbuhan, Kelangsungan Hudup dan Rasio RNA/DNA Udang Windu (Penaeus monodon, Fabr) - Akmal, A; Hasbullah, Dasep; Mundayana, Yuani; Rahmi, R; Hartanto, Nono (Journal Galung Tropika, 2020)
This engineering aims to determine the effect of the dose of vitamin plus administration on artificial feed on the growth, survival, and RNA / DNA ratio of tiger prawn larvae (Penaeus monodon, Fabr). The study was compiled using four vitamin Plus dose treatments, and each experimental unit had two cycles. The treatments used were: giving vitamin plus 5 mL/kg, 10 mL/kg, 15 mL/kg in artificial feed, and control without giving vitamin plus. The results showed that the average weight gain during tiger prawns’ engineering activity was observed to increase over time. Absolute growth of tiger prawns with the addition of vitamin plus dose of 15 mL/kg was the highest total growth, which was 101.77 ± 0.29 g, and the lowest was in control 83.07 ± 2.87 g. The highest daily growth rate was the addition of vitreous plus a dose of 10 mL/kg 1.47 ± 0.01% / day, and the lowest was the control, namely 1.10 ± 0.02% / day. Furthermore, the addition of vitamin plus with 10 mL/kg showed the highest survival value was 96.2 ± 1.6%, and the lowest was in control, namely 84.7 ± 0.6%. The highest to lowest survival rates were ten treatment doses, respectively; 15; 20 mL/kg, and control. The highest RNA / DNA ratio value of tiger prawns was produced at the addition of a dose of 15 mL/kg of 1.025 ± 0.029, and the lowest was at a quantity of 5 mL/kg, namely 0.618 ± 0.05.